A SYNTACTICAL ANALYSIS IN NON-STANDARD ENGLISH WORD OF MAC MILLER SONG LYRICS - Joko Wibowo (Universitas Al-Qolam Malang, 2022)
Every human being has at least one language, both spoken and written. The language contains basic or certain rules that form, combine, and express meaning that changes because words in language are combined differently through combinations in syntactic studies so that language has an important role in human life as a means of communication.This is actually the realization of the written examples.The Purpose of this research was to find out the non-standard and standard English words and to find out the tree structure in the Mac Miller song lyrics.Then, the writer choosessongs to analyze because studying songs does not just analyze the metaphorslanguage, word meaning and language style, but also analyze how non-standard English words can be used as standard English words by converting them with several tools such as phonological processes and basic grammar which in the song the English standard has been found the writer analyzessentence structureused in one of the lyrics to a song from Mac Miller's album entitled